Saturday

April 19, 2014

April 19, 2014

Posted by **Avik** on Sunday, February 3, 2013 at 3:17pm.

- Math -
**Reiny**, Sunday, February 3, 2013 at 5:03pmwhewww!

125x^4 + 20x^3 - 135x^2 - 10x + 2 + 6dy/dx = 0

at (-1,1)

125 - 20 - 135 + 10 - 2 + 6dy/dx = 0

6dy/dx = 22, so the slope of the tangent at (-1,1) is 22/6 = 11/3

equation of tangent:

1= (11/3)(-1) + b

b = 1 + 11/3 = 14/3

y = (11/3)x + 14/3 = (11x+14)/3

sub that into the original equation

25x^5+5x^4-45x^3-5x^2+2x+6y-24=0

25x^5+5x^4-45x^3-5x^2+2x+6(11x+14)/3-24=0

25x^5+5x^4-45x^3-5x^2 + 24x + 4=0

after dividing out the factor (x+1) we are left with

25x^4 - 20x^3 - 25x^2 +20x+4=0

tried to solve this, even had Wolfram page try it

http://www.wolframalpha.com/input/?i=25x%5E4+-+20x%5E3+-+25x%5E2+%2B20x%2B4%3D0

it gave me x = appr -.9507 and appr -.169872

If we sub those values into the derivative equation we should get -3/11 or -.2727..

I did not get that.

Can't find my error

OR,

those two points don't exist

(you might print out my solution and go through it to see if find any errors)

- Math -
**Steve**, Sunday, February 3, 2013 at 5:12pm-6y = 25x^5+5x^4-45x^3-5x^2+2x+24

y' = -1/6 (125x^4 + 20x^3 - 135x^2 - 10x + 2)

y'(-1) = 3

normal has slope -1/3

Go to http://rechneronline.de/function-graphs/

and plot

-1/6 * (25x^5+5x^4-45x^3-5x^2+2x-24)

and its derivative

as well as

3x+4

The line is not normal to the curve anywhere. Typo somewhere here?

- Math - PS -
**Steve**, Sunday, February 3, 2013 at 5:43pmWhen plotting the graphs, set

x: -2 to 2

y: -10 to 10

that will show things quite clearly.

**Related Questions**

Algebra - Rewrite the middle term as the sum of two terms and then factor ...

MATH - Solve system of equations algebraically. 1. 3x-3y=24 and 2x+5y=-37 2. -9x...

Math - Solve: 1.) 2x² + 24 = x² The answers I obtained were: x = i√24 and ...

Calculus - f(x)=(5x)/(1+2x^2). f'(4)=-75/289 f'(x)=(5-5x^2)/1+2x^2+x^4) Use this...

Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...

College Algebra - okay so using y = (-5/6)x + 3 how do i find the corresponding ...

math - Please check. (-6m^2n+3mn^2-5mn+2)+(4m^2n+2mn^2-6mn-9) Answer: -2m^2n+5mn...

math - Please check. (-6m^2n+3mn^2-5mn+2)+(4m^2n+2mn^2-6mn-9) Answer: -2m^2n+5mn...

Math - if f(x) = 2x^2 + 5x, find f(x+h) - f(x) / h and simplify. I started to ...

Algebra - Please let me know if I answered these correctly. thank you, #2. Add: ...